Pentakrifan halal menurut syara' dan perundangan di Malaysia: Satu tinjauan - Azhar, Alias; Abdul Wahab, Harlida (2017)
The concept of halal from the point of Sharia should be understood comprehensively. In the case of food products, halal (lawful/permissible) does not only mean edible products as prescribed by Islamic law but shall also include the meanings of 'good' or ‘thoyyib’ which is clean, hygienic, safe and of good quality. Food production shall include certain processes starting from the selection and preparation of ingredients, manufacturing processes, production itself, storage, transfer and distribution until being marketed to consumers.To ensure the halal aspect of a product, Malaysia provides a legal framework that covers both legal and institutional mechanisms by appointing authorities and special agencies for the purpose of implementation and enforcement of the law.The objective of this article is to study the meaning and concept of halalan thoyyiban and associate them with the interpretations of halal that contain in the legislative provisions together with its enforcement practices. Using a content analysis approach, the concept of halalan thoyyiban is elaborated by referring to the provisions of law that related to the aspect of halal for food products namely Trade Description Act 2011 and Food Act 1983.Interpretations and practices of halal is clearly in line with the real concept of halalan thoyyiba.Even some revisions to the legislation which fulfill the aspect of "thoyyiba" is considered as something very positive. It thus expressed the willingness and concern of the policy makers to jointly realize, implement and uphold "halalan thoyyiban" concept so as to meet the needs of Shari'ah.